Drug discovery in Africa : Impacts of genomics, natural products, traditional medicines, insights into medicinal chemistry, and technology platforms in pursuit of new drugs - Davies-Coleman, Mike; Masimirembwa, Collen; Chibale, Kelly (Springer Berlin Heidelberg, 2012)
Drug discovery originating in Africa has the potential to provide significantly improved treatment of endemic diseases such as malaria, tuberculosis and HIV/AIDS. This book critically reviews the current status of drug discovery research and development in Africa, for diseases that are a major threat to the health of people living in Africa. Compiled by leading African and international experts, this book presents the science and strategies of modern drug discovery. It explores how the use of natural products and traditional medicines can benefit from conventional drug discovery approaches, and proposes solutions to current technological, infrastructural, human resources, and economic challenges, which are presented when attempting to engage in full-scale drug discovery. Topics addressed are varied; from African medicinal plants to marine bioprospecting, pharmacogenetics and the use of nanotechnology. This book brings together for the first time a collection of strategies and techniques that need to be considered when developing drugs in an African setting. It is an unprecedented and truly international effort, highlighting the remarkable effort made so far in the area of drug discovery research by African scientists, and scientists from other parts of the world working on African health problems.